2010
DOI: 10.1038/ajg.2010.351
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Symptom Pattern of Pathologic Esophageal Acid Reflux in Patients With Functional Dyspepsia Based on the Rome III Criteria

Abstract: PEAR is present in almost one third of FD patients; the prevalence is ∼50% in those with epigastric burning. The "PPI test" has a limited value in distinguishing the FD patients with and those without PEAR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
56
0
6

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(64 citation statements)
references
References 11 publications
2
56
0
6
Order By: Relevance
“…18 In addition, epigastric pain or burning sensation may be associated with gastroesophageal reflux. 19,20 Therefore, gastric acid hypersecretion might result in EPS-related symptoms. These findings suggest that the extent or grade of atrophic gastritis can be involved in the generation of specific dyspeptic symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…18 In addition, epigastric pain or burning sensation may be associated with gastroesophageal reflux. 19,20 Therefore, gastric acid hypersecretion might result in EPS-related symptoms. These findings suggest that the extent or grade of atrophic gastritis can be involved in the generation of specific dyspeptic symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…There is a significant overlap in symptoms between GERD and FD, and studies have shown that many patients who are diagnosed with FD may have significant underlying pathological acid reflux into the distal esophagus. Tack et al [26] showed that acid reflux was present in 23% of patients diagnosed with FD according to the ROME II criteria, whilst Xiao et al [27] showed an even higher rate of 31.7% when using the ROME III criteria. Both studies have shown that FD patients with pathological acid reflux were more likely to have ‘ulcer-like' dyspepsia (Rome II classification) or EPS (Rome III classification).…”
Section: Epidemiological Changes Which May Be Contributing To Changesmentioning
confidence: 99%
“…One study [18] has shown that 37% of patients fulfilling the criteria for EPS also had esophageal acid reflux as determined by pH monitoring despite a normal endoscopy [18]. While further validation of the Rome III criteria for FD is needed, it will be the unraveling of the pathophysiology of this condition which will see a shift towards a more objective classification of FD.…”
Section: Epigastric Pain Syndromementioning
confidence: 99%